2022
DOI: 10.5603/gp.a2021.0224
|View full text |Cite
|
Sign up to set email alerts
|

Impact of advanced maternal age on maternal and neonatal outcomes in preterm birth

Abstract: Objectives:The aim of this study was to investigate the influence of advanced maternal age on the maternal and neonatal outcomes of preterm pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…From the medical point of view, the risk of miscar-riage increases with age, which is associated with a declining number and quality of egg cells. Advanced maternal age was a risk factor for adverse pregnancy outcomes as well [35]. On the other hand, from the perspective of developmental psychology, a woman is aware of the inevitability of the passage of time and, consequently, has a lesser ability to fulfil the parental role, which may have a negative impact on sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…From the medical point of view, the risk of miscar-riage increases with age, which is associated with a declining number and quality of egg cells. Advanced maternal age was a risk factor for adverse pregnancy outcomes as well [35]. On the other hand, from the perspective of developmental psychology, a woman is aware of the inevitability of the passage of time and, consequently, has a lesser ability to fulfil the parental role, which may have a negative impact on sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…Publication bias was investigated quantitatively using the Begg's test and publication bias was considered present if p > 0.05. 37 To obtain the p-values, a two-tailed test was used. The statistical analysis and graphs were presented with Reviewer Manager v. 5.3 and jamovi software v. 2.3 (https://www.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Specific patient characteristics, such as age 35 years or older, higher BMI, no insulin use, and so on, can increase the incidence of GDM (10,11). Moreover, the positive association between maternal age and preterm delivery in GDM remained significant, even after adjusting for relevant confounders (12). It has also been reported that maternal obesity was related to an increased risk of preterm delivery, but obese women with diabetes had an increased risk of preterm delivery, suggesting that blood glucose also plays a role while BMI affects preterm delivery (13).…”
Section: Introductionmentioning
confidence: 98%